Marine Antifouling for Underwater Archaeological Sites: TiO2 and Ag-Doped TiO2. (24th November 2013) - Ruffolo, Silvestro A.; Macchia, Andrea; La Russa, Mauro F.; Mazza, Lorenzo; Urzì, Clara; De Leo, Filomena; Barberio, Marianna; Crisci, Gino M.
Abstract : Marine fouling plays a crucial role in the degradation of underwater archaeological sites. Limitation of fouling activity and its damages are one of the most critical issues for archaeologists and conservators. The common cleaning procedure, consisting in the manual removal of fouling, requires a continuous maintenance, while a proper inhibition of biological colonisation would provide a long-time protection against biofouling. On the other hand, the most used antifouling paints, especially for ship hulls, show considerable toxicity level. Since submerged archaeological sites are often included in environmental protected areas, more eco-friendly products must be used. We have explored the possibility to use titanium dioxide and Ag-doped titanium dioxide as antifouling agents. For this purpose, they have been synthetized by sol-gel method, and then XRD, XPS, and reflectance spectroscopy measurements have been carried out to gain structural information. The powders have been dispersed in a polymer and then applied to marble surface to evaluate the chromatic alteration induced by the treatments. By means of biological tests, it was possible to assess their behaviour as biofouling agents. Results show a decreasing of biofouling activity on treated stony surfaces.